EFFECTIVE WAYS TO IMPROVE READING SKILLS (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
This article explores the development of reading skills,emphasizing the importance of acquiring knowledge, broadening perspectives, andfostering personal growth among readers. Additionally, it discusses variouseffective reading strategies that can benefit a wide range of readers